The Impact of Childhood Traumas on Academic Procrastination with Parent-Adolescent Conflict Mediation in Female Students - Moradi Dolatabadi, Mozhgan; Sobhi, Afsaneh; Ahmadi, Mohammad Saeid (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Academic procrastination is a prevalent issue among adolescents that can negatively impact their educational outcomes. This study aimed to investigate the effects of childhood traumas and parent-adolescent conflict on academic procrastination among female high school students in Karaj. It also sought to examine the potential mediating role of parent-adolescent conflict in the relationship between childhood traumas and academic procrastination. Methods and Materials: The study utilized a cross-sectional design with a sample of 384 female high school students selected via cluster random sampling from Karaj. Data collection was conducted using validated self-report questionnaires: the Childhood Trauma Questionnaire, the Conflict Behavior Questionnaire for assessing parent-adolescent conflict, and a standard Academic Procrastination scale. Descriptive and inferential statistical analyses, including correlation and regression analyses, were performed using structural equation modeling. Findings: The results indicated significant direct effects of childhood traumas and parent-adolescent conflict on academic procrastination. Specifically, higher levels of childhood traumas were associated with increased academic procrastination (β = .201, p < .001). Similarly, parent-adolescent conflict was positively correlated with procrastination (r = .25, p < .01). However, the indirect effect of childhood traumas on academic procrastination through parent-adolescent conflict was not significant (β = -.006, p = .747). Conclusion: This study underscores the impact of childhood traumas and parent-adolescent conflicts on academic procrastination. The findings highlight the importance of addressing these factors within educational and psychological interventions to support the academic success and well-being of students. Future research should explore longitudinal relationships and consider additional mediating variables.